PENGARUH MODEL PEMBELAJARAN INDEX CARD MATCH TERHADAP MOTIVASI BELAJAR PESERTA DIDIK KELAS VI DI SD NEGERI PANNARA KOTA MAKASSAR - Alfita Alia; Nuryamin; Mappasiara; Muhammad Amri; Erwin Hafid (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This thesis discusses the influence of the index card match learning model on the learning motivation of sixth grade students at Pannara Public Elementary School, Makassar City. This study aims to: (1) describe the index card match learning model of sixth grade students at Pannara Public Elementary School, Makassar City; (2) describe the learning motivation of sixth grade students at Pannara Public Elementary School, Makassar City; and (3) analyze the influence of the index card match learning model on the learning motivation of sixth grade students at Pannara Public Elementary School, Makassar City. This type of research is quantitative research with an ex post facto approach. This research was conducted at Pannara Public Elementary School, Makassar City. The population of this study was 65 sixth grade students, and the sample was taken using a saturated sampling technique. Data were collected through a questionnaire. The data analysis techniques used were descriptive statistical analysis and simple regression analysis. The implications of this study indicate that the Index Card Match learning model can be used as an alternative learning strategy to increase students' learning motivation through an active, interactive, and enjoyable learning atmosphere. Therefore, schools and educators are expected to support and implement innovative learning models to create a more effective and meaningful learning process.